2002
DOI: 10.1046/j.1525-139x.2002.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Review of the Pharmacokinetics of Vitamin D Analogues

Abstract: This article reviews the pharmacokinetic characteristics of calcitriol, paricalcitol, and doxercalciferol, and provides an overview of the metabolism of vitamin D. Calcitriol and paricalcitol have similar pharmacokinetic profiles, with terminal half-lives ranging from 5 to 10 hours in healthy subjects to 15-30 hours in patients undergoing dialysis. Both are active on intravenous administration and little of the active agent remains in the circulation after 24 hours, although they are normally given every 48-72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 14 publications
0
20
1
Order By: Relevance
“…Normally, 1,25(OH) 2 D 3 exists at low levels in blood after vitamin D intake (DeLuca, 1988). However, upon administration of the commercially available 1,25(OH) 2 D 3 via injection (calcitriol injection, Calcijex) or capsule (calcitriol, Rocaltrol) for the treatment of hypocalcemia, osteoporosis, hypoparathyroidism, hypoparathyroidism, osteomalacia, rickets, renal osteodystrophy (Bailie and Johnson, 2002), or cancer (Beer and Myrthue, 2006), high systemic levels of 1,25(OH) 2 D 3 are attained. Consequently, due to the marked toxicity associated with 1,25(OH) 2 D 3 , vitamin D analogs that possess less hypercalcemic effects and toxicity are being developed as new drug entities (Masuda and Jones, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Normally, 1,25(OH) 2 D 3 exists at low levels in blood after vitamin D intake (DeLuca, 1988). However, upon administration of the commercially available 1,25(OH) 2 D 3 via injection (calcitriol injection, Calcijex) or capsule (calcitriol, Rocaltrol) for the treatment of hypocalcemia, osteoporosis, hypoparathyroidism, hypoparathyroidism, osteomalacia, rickets, renal osteodystrophy (Bailie and Johnson, 2002), or cancer (Beer and Myrthue, 2006), high systemic levels of 1,25(OH) 2 D 3 are attained. Consequently, due to the marked toxicity associated with 1,25(OH) 2 D 3 , vitamin D analogs that possess less hypercalcemic effects and toxicity are being developed as new drug entities (Masuda and Jones, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, the average level of calcitriol is approximately 45 pg/ml (equivalent to about 0.1 n M ), while the precursor, 25(OH)D 3 , is at 29.6 ng/ml (about 74 n M ) [35]. Calcitriol suppresses the expression of parathyroid hormone with 50% inhibitory concentration in the sub-n M range [36], which is consistent with its endocrine function in mineral homeostatsis and bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical in vitro and in vivo studies demonstrated that paricalcitol has parathyroid hormone-suppressive activity similar to calcitriol (Calcijex TM ; 1α,25-dihydroxyvitamin D 3 ), but has less of an effect on serum calcium and phosphorus concentrations [1]. Paricalcitol pharmacokinetics have been investigated in healthy subjects and in subjects with chronic kidney disease [2]. Following intravenous administration, paricalcitol concentrations decrease rapidly during the first 2 h after a dose; thereafter, paricalcitol concentrations decline log-linearly with a half-life of about 7 h in healthy subjects and about 14 h in subjects with chronic kidney disease [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…Paricalcitol pharmacokinetics have been investigated in healthy subjects and in subjects with chronic kidney disease [2]. Following intravenous administration, paricalcitol concentrations decrease rapidly during the first 2 h after a dose; thereafter, paricalcitol concentrations decline log-linearly with a half-life of about 7 h in healthy subjects and about 14 h in subjects with chronic kidney disease [2, 3]. Other results in healthy subjects suggest that paricalcitol is extensively metabolized and is eliminated primarily by hepatobiliary excretion [3].…”
Section: Introductionmentioning
confidence: 99%